2021
DOI: 10.3389/fonc.2021.584213
|View full text |Cite
|
Sign up to set email alerts
|

A Four−Gene-Based Risk Score With High Prognostic Value in Gastric Cancer

Abstract: BackgroundGastric adenocarcinoma is an important contributor to cancer mortality and morbidity. This study aimed to explore the prognostic value of mutation patterns in gastric adenocarcinoma.Materials and MethodsWe extracted somatic mutation data for 437 gastric adenocarcinoma samples from The Cancer Genome Atlas (TCGA) Stomach Adenocarcinoma (STAD) cohort. Kaplan–Meier survival in the R package maftools was used to analyze associations between mutations and survival. Multivariate Cox proportional model was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…More than half of the patients cannot survive for more than 5 years owing to the heterogeneity of AML despite the development of AML risk stratification ( 7 ). AML prognostic stratification needs to be more precise so that as many patients as possible receive the treatment that is most appropriate for them ( 8 ). This study demonstrated that the risk stratification based on the eight-gene risk scoring system was consistent with the NCCN guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the patients cannot survive for more than 5 years owing to the heterogeneity of AML despite the development of AML risk stratification ( 7 ). AML prognostic stratification needs to be more precise so that as many patients as possible receive the treatment that is most appropriate for them ( 8 ). This study demonstrated that the risk stratification based on the eight-gene risk scoring system was consistent with the NCCN guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of SORCS3, it has been detected its methylation (53) and this epigenetic modification has been associated with the progression of gastric precancerous lesions (54). In the case of CCDC178, an study that performed whole genome sequencing in samples from a GC patient, identified in the primary GC tumor a somatic nonsynonymous single nucleotide variation affecting CCDC178 (55), and another study identified in GC mutations (mainly missense mutations and frame shift deletions) in CCDC178 that were significantly associated with poor survival (56).…”
Section: Discussionmentioning
confidence: 99%
“…In the process of gene signature establishment, besides univariate Cox regression analysis, a random survival forest algorithm was also applied for gene selection [ 33 ]; common angiogenesis-related genes selected by both approaches were further put into multivariate Cox regression analysis to develop ARS. In contrast with other clinicopathological factors, higher ARS consistently indicated poor prognosis of PCa patients, and it also has a promising ability in BCR prediction.…”
Section: Discussionmentioning
confidence: 99%